169k views
1 vote
Given: f(a)= a³ +a and g(a) = a -1 Find: (fog)(a)​

1 Answer

10 votes

Answer:

(fog)(a)​ = a³ - 3a² + 4a - 2

= (a - 1)×(a² - 2a + 2)

Explanation:

Given :

g(a) = a -1

f(a)= a³ +a

…………………………

(fog)(a)​ = f(g(a)​))

= g(a)³ + g(a)

= (a - 1)³ + (a - 1)

= (a³ - 3a² + 3a - 1) + (a - 1)

= a³ - 3a² + 3a - 1 + a - 1

= a³ - 3a² + 3a + a - 1 - 1

= a³ - 3a² + 4a - 2

Second method :

(fog)(a)​ = f(g(a)​))

= f(a - 1)

= (a - 1)³ + (a - 1)

= (a - 1)×[(a - 1)² + 1]

= (a - 1)×[a² - 2a + 1 + 1]

= (a - 1)×(a² - 2a + 2)

User JarrettV
by
6.5k points